Why Do Children Stay Out Of School In Indonesia? - Tatang Muttaqin; Rafael Wittek; Liesbet Heyse; Marijtje Van Duijn (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2017)
Municipal and household-level determinants for Indonesian children out of school are studied using multilevel analysis of 221,392 children in 136,182 households in 497 municipalities. The higher the poverty rate and public education expenditure per capita, the higher the likelihood that children drop out. However, a high(er) mean of municipality education expenditure significantly reduces children’s likelihood to never attend school while a high(er) poverty rate significantly increases the likelihood that children will never attend school. At the household level, expenditure, spending on education, and head of household’s educational background have a significant effect on reducing the number of children out of school.